Effect of fish-heavy metals contamination on the generation of reactive oxygen species and its implications on human health: a review - Wang, Yuxia; Noman, Anwar; Zhang, Chao; AL-Bukhaiti, Wedad Q.; Abed, Sherif M. (Frontiers in Marine Science, 2024)
Heavy metals (HMs) contamination significantly threatens plants, animals, aquatic ecosystems, and public health. HMs' accumulation in aquatic environments has become a serious environmental issue due to their high stability, bioaccumulation, and biomagnification properties. These metals enter ecosystems through both natural sources and/or human activities. The toxicity of HMs poses a threat to the aquaculture sector's sustainability by negatively affecting fish growth, reproduction, and overall physiology.Exposure to HMs in various forms can cause environmental damage, which may affect human health through direct poisoning symptoms or other adverse effects. One such effect is the increased production of reactive oxygen species (ROS), crucial metabolites that modulate the functions of pathogenic organisms and lead to oxidative stress. This, in turn, can contribute to the onset and exacerbation of numerous diseases that threaten human health. This review article examines the potential sources of HMs contamination in aquatic organisms, the impact of this contamination on the generation of ROS, and the implications for human health resulting from the consumption of contaminated aquatic products.